2023
DOI: 10.1155/2023/8807278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statins on Major Adverse Cardiovascular Events in Patients with Coronary Artery Spasm: A Meta-Analysis of the Asia Region

Abstract: Background. Whether statins can reduce major cardiovascular adverse events (MACE) in patients with coronary artery spasm (CAS) is controversial. And most of the relevant research to date has been conducted in Asia. Methods. We systematically searched electronic databases for studies on the effect of statins on MACE in patients with CAS in Asia and published up to September 2022. We included data on MACE in a statin therapy patient group and a no-statin therapy control group. We then evaluated the effect of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…In addition, in 2016, Ishii et al reported that statins were associated with a reduced rate of major adverse cardiac events in patients with CSA/ VSA 87) . In 2023, Zhao et al reported a meta-analysis that demonstrated the efficacy of statins for patients with CSA/ VSA 88) . In contrast, in 2019, Kim et al reported that atorvastatin and sarpogrelate did not produce any clinical effects 89) .…”
Section: Coronary Microvascular Testmentioning
confidence: 99%
“…In addition, in 2016, Ishii et al reported that statins were associated with a reduced rate of major adverse cardiac events in patients with CSA/ VSA 87) . In 2023, Zhao et al reported a meta-analysis that demonstrated the efficacy of statins for patients with CSA/ VSA 88) . In contrast, in 2019, Kim et al reported that atorvastatin and sarpogrelate did not produce any clinical effects 89) .…”
Section: Coronary Microvascular Testmentioning
confidence: 99%